Determination of enantiomer impurity in Bortezomib lyo injection formulation by using normal-phase liquid chromatography - Sanni Babu Najana; Hari Babu Bollikolla (SpringerOpen, 2021)
Abstract Background A highly stereo-specific liquid chromatographic technique was built up and authenticated to quantify the (1S,2R-enantiomer) impurity in Bortezomib lyo injection formulation. The separation was achieved on Chiral Pak ID-3 (3 μm, 4.6 × 250 mm) column ("amylose-based 3-chlorophenylcarbamate" chiral stationary phase) through a movable segment consisting of n-heptane, 2-propanol, ethyl alcohol, and TFA (82:15:3:0.1, v/v/v/v) at a flow rate of 0.6 mL/min. Column temperature preserved 25 °C, injection level 20 μL, sample cooler temperature ambient, and detection wavelength 270 nm. Results The retention time of (1S,2R-enantiomer) impurity and Bortezomib was determined 10.57 and 17.98 min, respectively. The resolution between (1S,2R-enantiomer) impurity and Bortezomib was found to be 4.2. The acceptance limit of the (1S,2R-enantiomer) impurity is 0.5%. The established method was authenticated as per ICH guidelines in respect of precision, accuracy, sensitivity, linearity, specificity, ruggedness, and robustness. The minimum quantity of the sample required for detection (LOD) was observed at 0.282 μg per mL and similarly the quantifying sample (LOQ) was observed to be 0.896 μg per mL. Conclusion The proposed normal phase-HPLC method that can quantify (1S,2R-enantiomer) impurity in Bortezomib lyo injection formulation at trace level concentration has been urbanized and authenticated as per ICH guidelines. The effectiveness of the technique was ensured by the specificity, exactitude, linearity, and accuracy. Hence, the method well suit for their intended purposes and can be successfully useful for regular analysis in laboratories and is suitable for the quality control.